Comparison Of Jakaba Growth With The Addition Of Organic Matter In Rice Washing Water - Yusminan Yusminan; Hilwa Walida; Fitra Syawal Harahap; Novilda Elizabeth Mustamu (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Jakaba (perennial luck mushroom) is a fungus derived from the fermentation of rice laundry water (leri). This fungus has the same physical shape as coral but has a fragile texture. This study aims to find out the growth of jakaba with the addition of organic matter in rice laundry water. The research was conducted in Padang Halaban village, Aek Kuo District, Labuhan Batu Utara Regency, North Sumatra. The research was conducted by mixing 1 liter of leri water with 400 grams of organic ingredients such as bran, banana peel and catfish feed Research was carried out by repeating each treatment as much as 6 repetitions with the parameters of salting, namely aroma, color, growth and diameter of jakaba. Based on observations, it is known that the growth of jakaba fungus occurs on the 12th day to the 15th day with the largest jakaba diameter which is 52.9 mm (P2) and the smallest is 40.25 mm (P1). The addition of other organic matter to leri water gives a different aroma and color of jakaba to each treatment.